1993
DOI: 10.1095/biolreprod49.3.609
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Gonadal Luteinizing Hormone and Follicle-Stimulating Hormone Receptors in the Fetal Pig and Related Changes in Gonadotropin and Testosterone Secretion1

Abstract: Fetuses of Large White and Meishan sows were collected at 28, 35, 49, 56, 75, 90, 103, and 113 days of gestation. LH, FSH, and testosterone concentrations were measured either in amniotic fluid (Days 28-56) or in arterial umbilical blood (Days 75-113). Gonads were analyzed for their content of LH and FSH receptors and RNA transcripts. Most of these parameters were similar in the two breeds, except that the mean testosterone concentration was higher (p < 0.05) in the plasma of 75-113-day Meishan fetuses (309 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
1
19
1
Order By: Relevance
“…In contrast to observations of the current study relative to FSH, Goxe et al (1993) reported no difference in serum FSH concentration and FSH receptor levels between MS and a White breed of pigs. However, these investigators also observed no difference in gonadal weights between the two breeds.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to observations of the current study relative to FSH, Goxe et al (1993) reported no difference in serum FSH concentration and FSH receptor levels between MS and a White breed of pigs. However, these investigators also observed no difference in gonadal weights between the two breeds.…”
Section: Discussioncontrasting
confidence: 99%
“…Littermates to each of these boars were castrated on 7, 14 and 25 dpp. These age groups represent early gonadotropin secretion in the porcine fetus (Liwska 1975, Goxe et al 1993) and the neonatal peak in gonadotropin secretion (Lunstra et al 1997). Procedures for handling all animals in this study complied with those specified in the Guide for the Care and Use of Agricultural Animals in Agricultural Research and Teaching (FASS 1999).…”
Section: Sample Collection and Histological Methodsmentioning
confidence: 99%
“…Additionally, the roles of FSH and LH in fetal ovarian maturation are currently under investigation (12,13). In fetal pigs, lower levels of FSH and LH receptor concentrations have been demonstrated in the ovaries compared to those in the fetal testes (13).…”
Section: Discussionmentioning
confidence: 99%
“…In fetal pigs, lower levels of FSH and LH receptor concentrations have been demonstrated in the ovaries compared to those in the fetal testes (13). It has been suggested that this dichotomous finding is responsible for the relative lack of fetal ovarian growth compared to fetal testicular growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, although FSHR has been detected in the fetal ovary of the pig [19] and cow [20], our understanding of the ontogeny and developmental expression of the FSHR in primates is incomplete [21,22]. The current study was designed in part to determine whether fetal ovarian folliculogenesis is associated with expression of FSHR.…”
Section: Introductionmentioning
confidence: 99%